Room-temperature exciton luminescence in II-VI quantum wells - HEGARTY, JOHN (My University, 1991)
We observe free excitons in absorption and emission at room temperature in Cd0,2sZne.7sTe/ ZnTe multiple quantum wells. A large overlap between luminescence and absorption peaks observed at 10 K is maintained up to room temperature showing that the luminescence is predominantly excitonic. From a rate equation analysis we calculate the branching ratio for free carriers relaxing into excitons to free-carrier radiative recombination.
PUBLISHED
Keywords: Physics